The Role of Guidance and Counseling Teachers in Overcoming The Impact of Bullying Behavior at SMPK ST. Theresia Kupang - Mali, Marli; Lio , Stefanus (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to describe the role of Guidance and Counseling teachers in dealing with the impact of bullying behavior on grade VIII students at SMPK St. Theresia Kupang, reviewed from psychological, social, and academic aspects. The research uses a descriptive qualitative approach through in-depth interviews, observations, and documentation studies. Data analysis was carried out using the Miles and Huberman interactive model, including data reduction, data presentation, and conclusion drawn, as well as data validity obtained through triangulation of sources and techniques. The results showed that the dominant form of bullying was mild verbal, social, and physical bullying which had an impact on reducing learning motivation, anxiety, and withdrawal from the social environment. Guidance and Counseling teachers play an important role through individual counseling, character building, mediation, and effective anti-bullying socialization. This intervention helps the victim recover from the emotional state and encourages changes in the perpetrator's behavior. The collaboration of Guidance and Counseling teachers, subject teachers, and students has proven to play a significant role in creating a safe and inclusive learning environment.